Orai1 mediates tumor-promoting store-operated Ca entry in human gastrointestinal stromal tumors via c-KIT and the extracellular signal–regulated kinase pathway - Lei Wang; Jiaqi Hao; Yijian Zhang; Ziyi Yang; Yang Cao; Wei Lu; Yijun Shu; Lin Jiang; Yunping Hu; Wenjie Lv; Yingbin Liu; Ping Dong (Tumor Biology)
Gastrointestinal stromal tumors originate from interstitial cells of Cajal, the pacemaker cells of the gut. Ca 2+ regulates the pacemaker activity of interstitial cells of Cajal. Store-operated Ca 2+ entry mediates the majority of Ca 2+ entry in most cancer cells and may be a factor in regulating intracellular Ca 2+ in interstitial cells of Cajal and gastrointestinal stromal tumors. Therefore, a blockade of this mechanism may affect the progression of gastrointestinal stromal tumors. Orai1 is the pore subunit of store-operated Ca 2+ channels. Here, we reported that Orai1 was overexpressed in gastrointestinal stromal tumor tissues and was positively correlated with a high-risk grade in gastrointestinal stromal tumor patients. Furthermore, upon Orai1 silencing, the functional store-operated Ca 2+ entry in gastrointestinal stromal tumor cells was decreased, indicating that the function of store-operated Ca 2+ entry was mediated by Orai1. Inhibition of Orai1-mediated store-operated Ca 2+ entry by Orai1 silencing or store-operated Ca 2+ entry blockers (SKF-96365 and 2-aminoethyl diphenylborate) induced obvious cell proliferation suppression, cell-cycle distribution, and apoptosis stimulation in GIST-T1 cells. Conversely, Orai1 overexpression increased store-operated Ca 2+ entry and cell proliferation in GIST882 cells. In addition, we found that activation of c-KIT and the extracellular signal–regulated kinase pathway participated in the oncogenic functions of Orai1-mediated store-operated Ca 2+ entry in gastrointestinal stromal tumor cells. These results revealed that Orai1-mediated store-operated Ca 2+ entry is critical for gastrointestinal stromal tumor cell proliferation via c-KIT and ERK signaling pathway activation. Orai1-mediated store-operated Ca 2+ entry plays an oncogenic role and may be a novel prognostic factor and therapeutic target for patients with gastrointestinal stromal tumors.